Biologically Important Areas II for cetaceans within U.S. and adjacent waters – Aleutian Islands and Bering Sea Region - Brower, Amelia; Ferguson, Megan; Clarke, Janet; Fujioka, Ei; DeLand, Sarah (Frontiers in Marine Science, 2022)
We delineated and scored Biologically Important Areas (BIAs) for cetaceans in the Aleutian Islands and Bering Sea region. BIAs represent areas and times in which cetaceans are known to concentrate for activities related to reproduction, feeding, and migration, and also the known ranges of small and resident populations. This effort, the second led by the National Oceanic and Atmospheric Administration (NOAA), uses structured elicitation principles to build upon the first version of NOAA’s BIAs (BIA I) for cetaceans. Supporting evidence for BIA II came from aerial-, land-, and vessel-based surveys; satellite-tagging data; passive acoustic monitoring; Indigenous knowledge; photo-identification data; whaling data, including stomach and fecal contents; prey studies; and genetics. In addition to narratives, maps, and metadata tables, the BIA II products incorporate a scoring and labeling system, which will improve their utility and interpretability. BIAs are compilations of the best available science and have no inherent regulatory authority. They have been used by NOAA, other federal agencies, and the public to support planning and marine mammal impact assessments, and to inform the development of conservation measures for cetaceans. In the Aleutian Islands and Bering Sea region, a total of 19 BIAs were identified, delineated, and scored for seven species, including bowhead, North Pacific right, gray, humpback, fin, and sperm whales, and belugas. These include one hierarchical BIA for belugas that consists of one localized “child” BIA within an overarching “parent” BIA. There were 15 feeding, 3 migratory, and 1 small and resident population BIAs; no reproductive BIAs were identified. In some instances, information existed about a species’ use of a particular area and time, but the information was insufficient to confidently delineate the candidate BIA; in those cases, the candidate BIA was added to a watch list. A total of 22 watch list areas were identified and delineated for 10 species, including all species mentioned above and minke whales, harbor porpoises, and Dall’s porpoises. There were 15 feeding, 4 migratory, 2 reproductive, and 1 small and resident population watch list areas. Some BIAs and watch list areas were transboundary between the Aleutian Islands and Bering Sea region and the Arctic region.